STRESS OXYDANT : INFLUENCE D’UNE COMPLEMENTATION NUTRITIONNELLE EN ANTIOXYDANTSET ADAPTATION A L’EXERCICE PHYSIQUE - Chiha, F; Benkara, Y; Sellami, A; Karouche, S (Journal of Human Sciences, 2016)
This study aims to highlight the knowledge of the state of oxidative stress, adaptation of athletes to oxidative stress and show the importance of supplementation with antioxidants for better support the health of athletes.The first step of the study is to analyze the literature to discuss the different results of the studies consulted. For the second part, an experimental study conducted at the end of a season play. 15 consenting swimmers aged between 10 and 16 years underwent measurements of anthropometric parameters and@O2max  achieved by the direct method to using a maximal exercise test using the protocol of Wasserman (1987) and biochemical parameters.The literature review focused the power of antioxidants to help against the effects of oxidative stress. The results of the experimentation revealed homogeneous BMI values and close to those of elite swimmers of the same age for the @O2max .The study revealed no changes in testosterone, CPK, LDH and cortisol. However, the report cortisol / testosterone increased significantly.According to the literature, it appears that the combined effects of antioxidants can help protect the Athlete's body against oxidative stress. At the end of the sports season, it seems that young swimmers would be adapted to the state of oxidative stress.